2000
DOI: 10.1523/jneurosci.20-24-09252.2000
|View full text |Cite
|
Sign up to set email alerts
|

Discharge Profiles of Juxtacellularly Labeled and Immunohistochemically Identified GABAergic Basal Forebrain Neurons Recorded in Association with the Electroencephalogram in Anesthetized Rats

Abstract: The basal forebrain ostensibly plays a dual role in the modulation of cortical activation and behavioral state. It is essential for stimulating cortical activation in association with waking (and paradoxical sleep), yet also important for attenuating cortical activation and promoting slow wave sleep. Using juxtacellular recording and labeling of neurons with Neurobiotin followed by immunohistochemical staining for glutamic acid decarboxylase (GAD), we studied the discharge properties of identified GABAergic ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
89
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 141 publications
(96 citation statements)
references
References 42 publications
7
89
0
Order By: Relevance
“…In the medial septumdiagonal band, Parv ϩ cells have been found to be fast spiking by in vitro recordings (Morris et al, 1999) and in the BF (in one cell) by in vivo recordings (Duque et al, 2000). In our in vivo recording studies, we identified a large number of cortically projecting GAD ϩ neurons that discharge tonically at relatively high rates (average Ͼ 30 Hz) in association with cortical activation (Manns et al, 2000a) and thus could correspond to the cortically projecting, Parv ϩ BF neurons identified here. ChAT ϩ cells that do not contain the CBPs in the rat brain (Kiss et al, 1990b(Kiss et al, , 1997Smith et al, 1994) discharge in a slow tonic manner and in a phasic bursting manner in association with cortical activation (Manns et al, 2000b).…”
Section: Functional Significance Of Cbp Content In Bf Cell Groupssupporting
confidence: 51%
See 1 more Smart Citation
“…In the medial septumdiagonal band, Parv ϩ cells have been found to be fast spiking by in vitro recordings (Morris et al, 1999) and in the BF (in one cell) by in vivo recordings (Duque et al, 2000). In our in vivo recording studies, we identified a large number of cortically projecting GAD ϩ neurons that discharge tonically at relatively high rates (average Ͼ 30 Hz) in association with cortical activation (Manns et al, 2000a) and thus could correspond to the cortically projecting, Parv ϩ BF neurons identified here. ChAT ϩ cells that do not contain the CBPs in the rat brain (Kiss et al, 1990b(Kiss et al, , 1997Smith et al, 1994) discharge in a slow tonic manner and in a phasic bursting manner in association with cortical activation (Manns et al, 2000b).…”
Section: Functional Significance Of Cbp Content In Bf Cell Groupssupporting
confidence: 51%
“…ChAT ϩ cells that do not contain the CBPs in the rat brain (Kiss et al, 1990b(Kiss et al, , 1997Smith et al, 1994) discharge in a slow tonic manner and in a phasic bursting manner in association with cortical activation (Manns et al, 2000b). Other cortically projecting BF neurons that were GAD Ϫ and presumed noncholinergic cells discharged tonically at a moderate rate and may correspond to Calb ϩ neurons (Manns et al, 2000a), which in other forebrain areas have been shown to discharge tonically (Li et al, 1995). Conversely, in the neocortex and hippocampus, Calb ϩ neurons displayed phasic discharge properties in addition to fast spiking Sik et al, 1995;Freund and Buzsaki, 1996).…”
Section: Functional Significance Of Cbp Content In Bf Cell Groupsmentioning
confidence: 99%
“…We consider this directional influence is to be mediated by a network that includes GABAergic ''S-max" BF neurons, which have been shown to be most highly active during SWS and are the major component of the BF sleep promoting system (Hassani et al, 2009). Interestingly, unit activity of BF ''S-max" and related cells has been linked to cortical delta waves that dominate the cortical EEG or LFP spectrum during SWS (Manns et al, 2000b;Lee et al, 2004), although this does not appear to be the case for all ''S-max" neurons (Hassani et al, 2009). Our findings suggest that BF gamma during SWS in fact is not functionally related to VC delta waves, as is the case for VC gamma.…”
Section: Discussionmentioning
confidence: 99%
“…Such studies have almost exclusively focused on recording the activity of single neurons, often labelled according to cell type, and linking their firing patterns to the cortical EEG (Duque et al, 2000;Manns et al, 2000aManns et al, , 2000bHassani et al, 2009), wake/sleep regulation (Szymusiak et al, 2000;Lee et al, 2004Lee et al, , 2005, aspects of sensory stimulation (Lin and Nicolelis, 2008;Nguyen and Lin, 2014), and behavioral task performance (Thomson et al, 2014;Tingley et al, 2014Tingley et al, , 2015. Convergent evidence (Zaborszky et al, 1999;Yang et al, 2014;Xu et al, 2015) indicates that BF contains multiple interconnected and heterogeneous networks, which operate as an ensemble to modulate cortical state and play distinct roles during sleep and wakefulness.…”
Section: Introductionmentioning
confidence: 99%
“…Other cholinergic nuclei such as the diagonal band of Broca or the nucleus basalis of Meynert could be stimulated; electrodes implanted in the noradrenergic locus coeruleus or GABAergic basal forebrain could improve mental alertness and attentional focus; serotonergic raphe nucleus stimulation might improve regulation of the time scale of reward prediction [86,89]. Other sites include the substantia nigra, caudate nucleus, nucleus accumbens, and the ventral tegmental area.…”
Section: Subcortical and Peripheral Stimulationmentioning
confidence: 99%